Composite thin film of simultaneously formed carbon and SnO2 QDs for supercapacitance application - Jadhav, Aarti; Patil, Sagar; Patil, Kashinath Rangu; Sathaye, Shivaram Dattatray; Rode, Chandrashekhar Vasant (New Journal of Chemistry, 2018)
Composite material with uniform size and structure is a critical asset that decides its properties like charge transfer, thermal, photoluminescence, mechanical, etc. and consequently the applications. Here for the first time, we report the concept of flame/combustion at liquid-liquid interface to synthesize in situ, thin film formation of composite consisting of two or more quantum dots. Synthesis of thin films of a composite containing C and SnO2 QDs having particle sizes below 3 nm was successfully done. As compared to a single quantum dots system, the formed composite showed significantly improved specific capacitance due to the synergistic effect arising from strong interaction between C and SnO2 QDs. This was confirmed by XPS, UV visible spectroscopy and photoluminescence spectra. Moreover, it was confirmed that even after 1000 charge/discharge cycles, the interaction between C and Sn remained unaltered; indicating significant stability of capacitance. Some of the advantages of this method include one step, eco-friendly process at ambient conditions. The generality of the method was established by synthesizing C-ZnO and C-TiO2 composite thin film. This new approach can be extended to form many other valuable composite thin films for various applications.

Friedel–crafts alkylation over Zr-mont catalyst for the production of diesel fuel precursors - Shinde, Suhas; Rode, Chandrashekhar Vasant (ACS Omega, 2018)
Heterogeneous Zr-Mont catalyst prepared by a simple protocol was employed for the production of diesel fuel precursors via Friedel–Crafts (FC) alkylation of petroleum-derived arenes (e.g., mesitylene, xylene, and toluene) with biomass-derived 5-(hydroxymethyl)furfural (HMF), HMF derivatives, and carbohydrates. Initially, several acidic catalysts were screened for the FC alkylation of mesitylene with HMF in nitroethane solvent. Among all, Zr-Mont catalyst gave an exceptionally high yield (80%) of mesitylmethylfurfural (MMF). The catalytic activity of Zr-Mont was also evaluated for the alkylation of different petroleum-derived arenes with ester/halogen derivatives of HMF. Suitable acid strength and high surface area of Zr-Mont were its major attributes to make it the most efficient solid acid catalyst for this FC reaction. Even after several reuses, the catalytic activity of Zr-Mont was found to be consistent, which was also evidenced by the acidity measurements of fresh and reused Zr-Mont catalysts by temperature-programmed desorption of ammonia and pyridine Fourier transform infrared spectroscopy techniques. Direct conversion of glucose to diesel fuel precursors was also attempted over Zr-Mont catalyst in mesitylene and polar nonacidic solvents at 150 °C. However, the activity of Zr-Mont catalyst was limited for glucose dehydration to HMF and MMF did not form. When the same experiment was performed in formic acid medium, MMF was produced in 34% yield. After the addition of formic acid, the reaction becomes biphasic which contains mesitylene as an organic phase and formic acid as an aqueous phase. Formic acid worked as a solvent, reactant, and cocatalyst, whereas mesitylene worked as a reactant and product extraction phase to enable easy product isolation. With this strategy, other diesel fuel precursors were also produced in 26–30% yields from glucose and different arenes. Similar strategy was successfully extended for the conversion of sucrose to diesel fuel precursors.

Influence of silver nanoparticles morphologies on density, viscosity and thermal conductivity of silver nanofluids and silver ionanofluids - Patil, Virendra Sudam; Andry, Cera-Manjarres; Salavera, Daniel; Rode, Chandrashekhar Vasant; Patil, Kashinath R; Coronas, Alberto (Journal of Nanofluids, 2018)
This paper explores the consequence of silver nanoparticles morphology (nanowires, nanoplates, and nanospheres) on density, viscosity and thermal conductivity of nanofluids and IoNanoFluids. Nuclear magnetic resonance spectroscopy results reveal that hydroxyl group in cation relates to silver nanoparticle surface of silver IoNanoFluid. Effect on bonding of silver nanoparticles after solvation in an ionic liquid was investigated with Infrared spectroscopy. UV-Visible spectroscopy analysis observed variations in color and optical properties of silver IoNanoFluids compared with nanofluids. Structural and morphological characterization of silver nanofluids and silver IoNanoFluids were carried out with Scanning electron microscopy and Transmission electron microscopy techniques. The presence of silver nanoparticles from the aqueous phase of nanofluids to viscous ionic liquid phase was confirmed by X-ray photoelectron spectroscopy and Energy dispersive analysis. The thermal stability study unveils that Choline bis(trifluromethylsulfonyl)imide ionic liquid, and its derived silver IoNanoFluids, are more stable than silver nanofluids. There was no considerable impact was observed for the silver nanoparticles morphology on the density of IoNanofluids. Moreover, two-dimensional silver structures raise the viscosity further compare to other two morphologies of silver nanoparticles in a base ionic liquid. Among all three studied morphologies, silver nanowires influence additional in the enhancement of thermal conductivity for silver nanofluids and IoNanoFluids. Enhanced thermal conductivity and reduced viscosity of silver nanowires based IoNanoFluid sorts this fluid as a potential heat transfer fluid.

Ti-doped Pd-Au catalysts for one-pot hydrogenation and ring opening of furfural - Date, Nandan Shreehari; La Parola, Valeria; Rode, Chandrashekhar Vasant; Testa, Maria Luisa (Catalysts, 2018)
Pd-Au bimetallic catalysts with different Pd/Au atomic ratios, supported on ordered structured silica (Hexagonal mesoporous silica-HMS, or Santa Barbara Amorphous-15-SBA-15) were evaluated for one-pot hydrogenation of furfural to 1,2-pentanediol. The surface and structural properties of the catalysts were deeply investigated by X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), N-2 adsorption isotherms (BET), Infrared spectroscopy (IR), and acid capacity measurements. XPS studies revealed that Ti doped supports had higher dispersion of the active phase, particularly in the case of Pd-Au materials in which Ti played an important role in stabilizing the metallic species. Among the various process conditions studied, such as temperature (160 degrees C), catalyst amount (10% w/w), and reaction time (5 h), H-2 pressure (500 psi) was found to improve the 1,2-pentanediol selectivity. The SBA silica bimetallic Ti-doped system showed the best performance in terms of stability and reusability, after multiple cycles. Under specific reaction conditions, the synergism between Pd-Au alloy and Ti doping of the support allowed the ring opening pathway towards the formation of 1,2-pentanediol in furfural hydrogenation.
Keywords: Bimetallic catalyst; furfural; Hydrogenation; ring-opening

2,5-Diformylfuran—an oxidation product of 5-hydroxymethylfurfural - Shinde, Suhas Hanmant; Rode, Chandrashekhar Vasant (2,5-Diformylfuran—an oxidation product of 5-hydroxymethylfurfural, 2020)
In the current scenario of depleting fossil-derived resources, biomass is considered a potential feedstock for sustainable energy supply and production of alternative chemicals. Among them, 2,5-diformylfuran (DFF) is one of the most important chemicals having widespread potential applications. DFF is produced from bioderived resources through the catalytic oxidation process. In this chapter, catalytic routes for the production of DFF starting from biomass-derived furan derivatives and sugars (e.g., mono/polysaccharides) are discussed in detail. Comprehensive emphasis is given to the catalysts (e.g., homogeneous and heterogeneous) and enzymes used for the transformation of various bioderived sources into DFF. Moreover, a brief look has also been given at the transformations and applications of DFF.
Keywords: 2; 5-Diformylfuran; 5-Hydroxymethylfurfural Biomass; Catalysis Chemicals; Oxidation Sugars